An empirical study on the influence of perceived organizational support on academic expatriates’ organizational commitment - Yahya, Khulida Kirana; Mansor, Fairuzah; Warokka, Ari (IBIMA Publishing, 2012)
The paper aims to examine the relationships between the perceived organizational support and expatriates' organizational commitment.A total of 131 questionnaires was distributed to expatriate who are currently serving at a public university and a sample of 93 returned-questionnaires was used for further analysis. The data were analyzed using Pearson's correlation and regression analysis to investigate the relationship perceived organizational support and organizational commitment.The correlation analysis proved that the perceived organizational support was highly important to affective and normative commitment whereas its relationship with continuance commitment is not relevant. Finally, the regression analysis revealed perceived organizational support as being more significant at influencing organizational commitment. Furthermore, the regression results also showed that 40.6 % of total variance of POS was explained by organizational commitment.This denotes that POS play a vital role in promoting organizational commitment.In addition, discussions, implications, as well as conclusions of the study were also highlighted.